An integrated approach for on-demand dynamic capacity management service in U-space - Tang, Yiwen; Xu, Yan; Inalhan, Gokhan (IEEE, 2022)
This paper presents an integrated approach for on-demand Dynamic Capacity Management (DCM) service to be offered in U-space. The approach involves three main threads, including flight planning (demand), airspace configuration (capacity) and demand-capacity balancing (DCB). The flight planning thread produces UAS (unmanned aerial systems) trajectories for each flight that together reflect the estimated traffic demand. The airspace configuration thread defines the fundamental airspace structure and proposes dynamic adjustment schemes that determine the capacity distribution. It also enables the flight planning to reschedule alternative trajectory options to route away from possible congested areas. The last DCB thread takes the previous inputs and then computes for the optimal slot allocation and trajectory selection, as well as the optimal airspace configuration. Simulation case studies have been performed through mimicking an envisioned U-space operating scenario. Results suggest that the integrated approach can achieve the best outcome in almost all the key performance areas than any other cases where only partial functions are realised.
Keywords: airspace configuration; demand-capacity balancing; Dynamic Capacity Management; UAS traffic management; Uspace